Functional Treatment of Isolated Stable Weber B Fractures of the Lateral Malleolus with Immediate Weightbearing and Joint Mobilization. - Danilo Ryuko Cândido Nishikawa; Fernando Aires Duarte; Guilherme Honda Saito; Eric Sarau Sorbini; Vitor Sequim; Pedro Augusto Pontin; Fabio Correa Paiva Fonseca; Bruno Rodrigues Miranda; Alberto Abussamra Moreira Mendes; Marcelo Pires Prado (Journal of the Foot & Ankle)
Objective: This study aimed to evaluate the clinical and radiographic outcomes of conservative treatment in patients with isolated Weber B fractures of the lateral malleolus. Methods: Medical charts of 30 patients with isolated and stable Weber B fractures of the lateral malleolus, exhibiting less than 2mm of displacement, were retrospectively evaluated. All patients underwent early weightbearing and joint mobilization, with treatment involving the use of a cam-walker boot (CWB) for a period of 6 to 8 weeks. Clinically, qualitative variables such as the presence of residual pain, tibiotalar joint motion, and total return to physical activities were evaluated. Radiographic parameters included bone healing time, healing rate and fracture displacement. Results: Among the 30 patients, 6 (20%) experienced residual pain, while 25 (83%) successfully resumed their previous physical activities within an average period of 3.4 months. Limited joint mobility was observed in 6 (20%) patients. Radiographically, 22 (73.3%) had fracture deviation of 1 mm, 6 (20%) of 2 mm, and 2 (6.7%) showed no deviation. The average time for bone healing was 7 weeks. Three (10%) patients developed pseudarthrosis. Return to physical activities was correlated with time and rate for fracture healing. Residual pain was associated with pseudarthrosis, dyslipidemia, and hypothyroidism. Bone healing did not correlate with age, displacement or comorbidities. Conclusion: The present study demonstrated that the proposed conservative treatment yielded satisfactory clinical and radiographic results, with a high rate of bone healing and successful return to previous physical activities. Level of Evidence IV; Retrospective case series.